Flow Customizer: An Algorithm to Design Lean-Flow Production Systems for Mass Customization - Chatzopoulos, Christos G. (International Journal of Industrial Engineering and Management, 2014)
The design of a production system in Mass Customization contexts is difficult due to product variability. This variability creates a complicated situation to engineers and Mass Customizers. This situation needs to be decoded, analysed and simplified. The present paper proposes an algorithmic procedure for designing a Lean-Flow Production System inMass Customization contexts, named as Flow Customizer. The Flow Customizer adopts Continuous Flow Manufacturingand Demand Flow Technologyapproaches. They provide the fundamentals for designing demand drivencontinuous and mixed-model production flow.The outcome of the Flow Customizer is to create Production Modules that are connected to each other through Kanban system. The application of the algorithmic procedure is illustrated by an example that simplifies data taken from an actual context. Article history: Received (20.08.2014); Revised (14.11.2014); Accepted (23.11.2014)